Pengaruh Net Interest Margin (NIM) Dan Likuiditas Terhadap Capital Adequacy Ratio (CAR) Pada Bank Yang Terdaftar Di Bursa Efek Indonesia - Marpaung, Annaria Magdalena; ., Lizabeth (LPPM Institut Bisnis dan Informatika Kesatuan, 2018)
Sudirman (2013:93) opined that banks are obliged to provide minimum capital as of 8 (eight) percent. This can be measured using Capital Adequacy Ratio (CAR). CAR is a ratio calculated from the amount of Bank’s capital compared to ATMR. CAR is an indicator of Bank ability to cover its depreciated assets. This is a result from loss, due to risque assets (Dendawijaya, 2005). Fund distribution to the society in the form of loans is a Bank main actitivy other than collecting the fund from third party. The increase in revenues will result in the increasing of capital, such is with an assumption that the earned revenues are reinvested into capitals. In accordance to this, then Net Interest Margin (NIM)is being used to acquire the Bank management ability in managing its productive assets in order to produce net profit. Liquidity ratios are used to measure a Bank ability in fulfilling its short term when due (Kasmir, 2009). The larger the ratios, the more liquid the assets. The relationships of capital and liquidty is firm enough, the Bank does not need to obtain other source of capital to fulfill its short term obligations.